Synthesis and Thermal Characterization of new interpenetrating polymer network (IPN) Silicone- Epoxy Resins - Ali M. Abdulla (Journal of Global Pharma Technology, 2019)
Polymers are widely used in industry and in our daily life because of their diverse functionality, light weight, low cost and excellent chemical stability. However, on some applications such as heat exchangers and electronic packaging, the low thermal conductivity of polymers is one of the major technological barriers. Interpenetrating polymer network (IPN) is a novel type of polymer hybrids, which possess physicochemical properties suitable for high performance coating. Heat resistance IPN have been prepared from immiscible resins , epoxy and silicones using a cross-linking agent and a catalyst. The products were analyzed by, FTIR, TGA, DSC, UV-Vis and SEM studies .It was different from those of the individual resins. Silicone micro domains could be seen uniformly distributed in epoxy regions. Keywords: Silicone-Epoxy Resins, Interpenetrating polymer network (IPN), Polymer.